Optimizing the pre-treatment of kenaf bast - Seeni Mohamed, Nurhafizah; Anuar, Hazleen; Mel, Maizirwan; Mohd. Sibi, Nurhanis (2011)
Kenaf (Hibiscus cannabinus) is a warm season annual fiber crop which is found to be the best alternative plant to substitute the raw material for lactic acid production due to its short period of harvest time and process high quality cellulose. It is a lignocellulosic material which is naturally resistant to breakdown to its structural sugars that will inhibit microorganisms to be accessed through. Therefore, it needs to undergo pre - treatment process either by mild acid hydrolysis or base hydrolysis in order to liberate glucose. Basically, three solvents such as sodium hydroxide (NaOH), sulfuric acid (H2SO4) and ammonium hydroxide (NH4OH) were used to determine the best method for pre-treatment process and the result is H2SO4 which gave 9.83% of glucose conversion or 2.95 g/L glucose. The maximum result that was obtained during optimization process to produce glucose is 8.65 g/L, equivalent to 21.63 percent glucose conversion.